2022
DOI: 10.1007/s00265-022-03207-4
|View full text |Cite
|
Sign up to set email alerts
|

Aggression and multi-modal signaling in noise in a common urban songbird

Abstract: Anthropogenic noise may disrupt signals used to mediate aggressive interactions, leading to more physical aggression between opponents. One solution to this problem is to switch signaling effort to a less noisy modality (e.g., the visual modality). In the present study we investigate aggressive behaviors and signaling in urban and rural male European robins (Erithacus rubecula) in response to simulated intrusions with or without experimental noise.First, we predicted that urban birds, living in noisier habitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…In the present study, we asked whether Galápagos yellow warblers show increased aggression and flexibility in their song when faced with a simulated intruder in experimentally increased noise. Unlike some of the previous studies showing an increase in aggression levels with increasing ambient noise (Akçay et al, 2020; Davies & Sewall, 2016; Phillips & Derryberry, 2018), or experimental noise (Grabarczyk EE & Gill, 2019; Önsal et al, 2022) we found no effect of experimental traffic noise on physical aggression. Instead, we found that birds on Santa Cruz sang songs with significantly higher minimum frequency than birds on Floreana and, when experimentally exposed to traffic noise, birds in both islands increased the minimum frequency of their songs.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the present study, we asked whether Galápagos yellow warblers show increased aggression and flexibility in their song when faced with a simulated intruder in experimentally increased noise. Unlike some of the previous studies showing an increase in aggression levels with increasing ambient noise (Akçay et al, 2020; Davies & Sewall, 2016; Phillips & Derryberry, 2018), or experimental noise (Grabarczyk EE & Gill, 2019; Önsal et al, 2022) we found no effect of experimental traffic noise on physical aggression. Instead, we found that birds on Santa Cruz sang songs with significantly higher minimum frequency than birds on Floreana and, when experimentally exposed to traffic noise, birds in both islands increased the minimum frequency of their songs.…”
Section: Discussioncontrasting
confidence: 99%
“…It is also possible that yellow warblers use signals in other modalities (such as visual modality, e.g. wing-out and tail-spread display) more effectively in increased noise (Akçay & Beecher, 2019; Önsal et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anemone fish ( Amphiprion chrysopterus [ 80 ]) exposed to intermittent motorboat noise stayed closer to their anemone and responded with increased territorial aggression toward heterospecifics [ 81 ]. When anthropogenic noise increased in rural territories, the European Robin ( Erithacus rubecula [ 14 ]) displayed an increase in aggression [ 82 ]. Urban robins responded with more behaviors that are aggressive to simulated intrusions.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it could mask parent-offspring communication, hamper the transmission of mate quality information through bird songs, reduce the quality of the territory, induce physiological stress in chicks, impair their development [54], and alter the perceptions of predators [55] or prey [56]. Noise can also induce shifts in the frequency of vocal signals to visual or physical ones [57], direct modifications of song characteristics, higher frequencies of bird singing in noisy environments [58], and even the cultural evolution of songs [59,60]. However, tolerance to noise and other human disturbances varies across species and should also reflect adaptations to urban environments, as the consequence of species turnover is not random [56].…”
Section: Discussionmentioning
confidence: 99%